PENERAPAN MODEL COOPERATIVE LEARNING TIPE COOPERATIVE INTEGRATED READING AND COMPOSATION (CIRC) UNTUK MENINGKATKAN KETERAMPILAN MENYELESAIKAN SOAL CERITA DI KELAS IX SMP NEGERI 7 MUARA BUNGO - Daswati Daswati (Jurnal Muara Pendidikan, 2019)
This study aims to improve students' skills in solving story problems in class IX of SMP Negeri 7 Muara Bungo by using the Cooperative Integrated Reading And Composation method. This type of research is Class Action Research (CAR). The subjects of this study were grade IX students of SMP Negeri 7 Muara Bungo. PTK research procedures include; (1) Planning (determining the number of cycles and subject matter to be studied, determining research samples, preparing lesson plans and assessment instruments, arranging other observation formats), (2) Action (carrying out 3 class actions referring to planning), (3 ) Observing (observing the development of cognitive, affective, and psychomotor abilities and group performance), (4) Reflection (carrying out data analysis and reflection on the application of learning models, process evaluation and learning outcomes). The results of the study obtained that the application of Cooperative Learning type CIRC can improve students' skills in solving story problems. The results of the study obtained that the application of Cooperative Learning type CIRC can improve students' skills in solving story problems. Students' skills in solving story problems always increase from each cycle, in the first cycle the score is 0.03 with a low category, the second cycle is 0.05 with a moderate category and the third cycle 0.079 with a high category. Then the application of Cooperative Learning type CIRC can improve mathematics learning outcomes with an average value of the first cycle of 56.58 up to 66.71 in the second cycle and a high increase in the third cycle 71.97.